PRODUKTIVITAS SAPI BALI JANTAN DIPELIHARA PADA LAHAN GAMBUT BASAH - Kristyan Amiano; Yemima Yemima; Dwi Dedeh Kurniasari (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
This study aims to evaluate male Bali cattle as potential livestock on peatlands. This research was conducted from October 2020 to December 2020. The method used in this study was a survey in the form of direct observation and measurement of livestock to obtain primary data. The sample of the area was taken by purposive sampling based on the largest Balinese cattle population in wet peatlands, with a total of 60 male Bali cattle. The variables observed included variables, body length (cm), shoulder height (cm), chest circumference (cm), body weight (kg), forage characteristics, and seedlings based on SNI-2017 for Bali cattle. The data obtained were analyzed descriptively by calculating the average value and standard deviation. The results show that the maintenance of male Bali cattle on wet peatlands can utilize natural greenery so that it can reduce production costs. The performance of male Bali cattle production can be seen as the criteria for selecting superior male seedlings in wet peatlands, where the percentage of entering class I was 33.4% of the total population being maintained. Wet peatlands can be used as a source of Balinese cattle to meet the need for productive beef cattle.